(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Age is one of the important pillars in the establishment of personal identity of an individual required in civil and criminal cases during life and after death. It becomes more important in developing countries where birth records are poorly maintained. Among all other age determinants, radiological examination of bone for appearance and fusion of ossification centers is rated to be a more accurate and reliable method for assessment of skeletal maturity by the legal and medical authorities as the union of epiphysis with the respective diaphysis of that bone occurs during an age period which is almost specific for that particular bone. Aims and Objectives: The objective of this study was to assess skeletal maturity of ischial tuberosity by radiological examination for a known chronological age of the subjects with age bracket 17-25 years atShalamar Hospital Lahore. Materials and Methods: The present cross sectional survey study was conducted in the radiology department of Shalamar Hospital Lahore in 200 subjects of both genders of 17 – 25 years, having known date of birth using Digital X-Rays machine to evaluate the fusion of ischial tuberosity. Cases were selected after ruling out the nutritional, developmental and endocrinal pathology which affects the skeletal development. Data analysis was done using SPSS Version 23.Conclusions were drawn and compared with available results of previous work done in this field. Results and Observations: Out of 200 subjects, there were 132 males (66 %) and 68 females (34%).The mean ± SD age of both genders was 21.24± 2.77. The mean ± SD age of complete union for ischial tuberosity amongst males was 21.52± 2.77 years and amongst females was 20.69 ± 2.72 years with p value < 0.05. Conclusion: The fusion of ischial tuberosity is not affected by ethnicity. Factors like diet and nutrition directly affect bone growth and hence bone age. More studies should be conducted across the country to formulate a standard in setting up a uniform criterion for assessing age of adolescents.